A randomized placebo-controlled PET study of ketamine´s effect on serotonin1B receptor binding in patients with SSRI-resistant depression - Tiger, Mikael; Veldman, Emma R.; Ekman, Carl-Johan; Halldin, Christer; Svenningsson, Per; Lundberg, Johan (Translational psychiatry, 2020)
The glutamate N -methyl- d -aspartate receptor antagonist ketamine has a rapid antidepressant effect. Despite large research efforts, ketamine’s mechanism of action in major depressive disorder (MDD) has still not been determined. In rodents, the antidepressant properties of ketamine were found to be dependent on both the α-amino-3-hydroxy-5-methylisoxazole-4-propionic acid (AMPA) and the serotonin (5-HT) 1B receptor. Low 5-HT 1B receptor binding in limbic brain regions is a replicated finding in MDD. In non-human primates, AMPA-dependent increase in 5-HT 1B receptor binding in the ventral striatum (VST) has been demonstrated after ketamine infusion. Thirty selective serotonin reuptake inhibitor-resistant MDD patients were recruited via advertisement and randomized to double-blind monotherapy with 0.5 mg/kg ketamine or placebo infusion. The patients were examined with the 5-HT 1B receptor selective radioligand [ 11 C]AZ10419369 and positron emission tomography (PET) before and 24–72 h after treatment. 5-HT 1B receptor binding did not significantly alter in patients treated with ketamine compared with placebo. An increase in 5-HT 1B receptor binding with 16.7 % ( p = 0.036) was found in the hippocampus after one ketamine treatment. 5-HT 1B receptor binding in VST at baseline correlated with MDD symptom ratings ( r = −0.426, p = 0.019) and with reduction of depressive symptoms with ketamine ( r = −0.644, p = 0.002). In conclusion, reduction of depressive symptoms in MDD patients after ketamine treatment is correlated inversely with baseline 5-HT 1B receptor binding in VST. Further studies examining the role of 5-HT 1B receptors in the antidepressant mechanism of action of ketamine should be conducted, homing in on the 5-HT 1B receptor as an MDD treatment response marker.